SAGUNA BRAHMAN DALAM TEKS KAá¹¬HA UPANIá¹¢AD DAN IMPLEMENTASINYA BAGI PRAKTIK AGAMA HINDU DI BALI - Sari, Ni Luh Komang Indah (PANGKAJA: JURNAL AGAMA HINDU, 2020)
This article describes one source of Hindu theology, Kaá¹ha Upaniá¹£ad. The Kaá¹ha Upaniá¹£ad is examined in the scope of scientific Brahmavidya to discover the Saguna Brahman concept in it. The study also examined aspects of implementation in the practice of Hinduism in Bali. The values of local wisdom in Balinese Hindu society actually have harmony with the principles and philosophy of the Vedas. The use of Acintya as Nirguna God in the Hindu version of Bali actually actually has the signs of the Saguna Brahman which is the fusion of the Nirguna Brahman concept into the Saguna Brahman. The implementation of Saguna Brahman in Balinese Hindu practices can be seen in the manifestation of Tri Hita Karana whose principle is to manifest love for the universe, while the universe is the embodiment of God.Â